Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci - de las Fuentes, Lisa; Schwander, Karen L.; Brown, Michael R.; Bentley, Amy R.; Winkler, Thomas W.; Sung, Yun Ju; Munroe, Patricia B.; Miller, Clint L.; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M.; Bielak, Lawrence F.; et al. (Frontiers in Genetics, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226 315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant (P < 5 x 10 -8 ) and suggestive (P < 1×10 -6 ) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117 531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (FOXP1, MBOAT4, SKP2, STIM1, STX4), brain (BRI3,